Forum Pemasyarakatan Hasil-Hasil KTT IV ASEAN : himpunan bahan-bahan (Departemen Perdagangan, 1992)
Enhancement of public awareness of the decisions of the 4th ASEAN Conference regarding Common Effective Preferential Tariff (CEPT); results of a forum.